Poisoning by Ateleia glazioviana (Leg. Papilionoideae) in cattle Intoxicação por Ateleia glazioviana (Leg. Papilionoideae) em bovinos - Gava A.* (2001)
A disease affecting cattle from western Santa Catarina and northwestern Rio Grande do Sul, characterized by nervous and caradiovascular manifestations, is described. The animals succumbed by "sudden death" or showed subcutaneous pendant edema and engorged pulsating jugular veins, preceded or not by apathy, lethargy and blindness. The disease affects cattle over 1 year of age and occurs mainly during fall and winter. Morbidity rates are 10-60% and mortality may be up to 95%. Gross lesions include pale and firm areas in the myocardium, mainly along the coronary vessels and extending into the septum. In part of the animals, the liver is enlarged and has a nutmeg appearance. Histopathological changes include swelling and necrosis of cardiac myofibers, and interstitial fibrosis and macrophagic infiltrate in the cardiac muscle, as well as severe centrolobular congestion and slight fibrosis in the liver. In the white matter of the brain of animals that showed clinical signs of lethargy, spongy degeneration (status spongiosus) is seen. The disease with lethargic manifestations was reproduced experimentally in cattle by feeding the leaves of Ateleia glaziovana in single doses of 40 and 50 g/kg and subdivided daily doses of 2.5, 5.0, 7.5 and 10 g/kg over long periods, with the initial dose of 1g/kg, additioned by 1g/kg/day till reaching 15g/kg, totaling 120 g/kg.